Francisk Skorina, Wroclaw and Adam Dyon: Book Migration and the First Paleotype of the Grand Duchy of Lithuania - Morozova, Nadežda; Parshenkov, Aleksandr (Slavistica Vilnensis, 2025)
This article provides an analysis of the early history of a copy of Akathists by Francisk Skorina, held in the Wroclaw University Library, along with a detailed examination of the edition’s specific decorative features. Evidence is presented demonstrating that this copy of the Akathists formerly belonged to Daniel Prinz von Buchau.Through a thorough study of the historical context, the authors conclude that Skorina employed se condary printed materials in the production of his Akathists.The hypothesis regarding the possible Nuremberg origin of certain decorative elements in Skorina’s edition of Akathists is supported by the findings presented in this article. The information also substantiates the assumption that Skorina spent time in Wroclaw and engaged with local publishers. Furthermore, it is demonstrated that parts of The Little Traveller’s Book could not have been printed in Prague. This article is the first to publish scientifically verified information about the connection between Francisk Skorina and Adam Dyon, and it includes images of decorative elements shared by both printers. Additionally, it suggests the possibility that Skorina utilized materials from the Leipzig printer Martin Landsberg in his work. The arguments presented provide a robust basis for confirming the chronology of the first paleotype of the Grand Duchy of Lithuania.
Keywords: Francisk Skorina; Daniel Prinz von Buchau; Adam Dyon; Akathists of Francisk Skorina; Vilnius Gospel of 1575; early printed Cyrillic editions; Grand Duchy of Lithuania; Wroclaw University Library